2004
DOI: 10.1046/j.1398-9995.2003.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE antibody to Aspergillus fumigatus recombinant allergens in cystic fibrosis patients with allergic bronchopulmonary aspergillosis

Abstract: Immunoglobulin E reactivity to a panel of purified Af allergens, especially to Asp f3 and f4, differentiates ABPA from atopic Af ST+ non-ABPA CF patients. Serial determinations of IgE reactivity to individual purified Aspergillus antigens, especially Asp f3, demonstrates that increases in IgE reactivity may provide improved distinction between stages of flares and remission compared with changes in IgE reactivity to a crude Aspergillus extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 12 publications
1
58
2
2
Order By: Relevance
“…Other authors (11) have reported that rAspf3 and rAspf4 allow discrimination between ABPA and non-ABPA patients with atopic A. fumigatus-positive skin tests. According to the data in the literature (2,11,21), rAspf4 (a cytoplasmic protein with unknown function) and rAspf6 recombinants have provided powerful tools for the accurate diagnosis of ABPA. Kraemer et al (13) have shown that allergen-specific IgE against these two recombinants could be detected almost exclusively in the sera of patients with ABPA.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors (11) have reported that rAspf3 and rAspf4 allow discrimination between ABPA and non-ABPA patients with atopic A. fumigatus-positive skin tests. According to the data in the literature (2,11,21), rAspf4 (a cytoplasmic protein with unknown function) and rAspf6 recombinants have provided powerful tools for the accurate diagnosis of ABPA. Kraemer et al (13) have shown that allergen-specific IgE against these two recombinants could be detected almost exclusively in the sera of patients with ABPA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, specific IgE against rAsp f were used. The development of antibodies to recombinant allergens has recently been reported [5,12,15] and shows an improvement in diagnosis as well as the capacity to distinguish between ABPA patients (even during remission) and AFS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The DCs form an immune sensory mesh surrounding the airway, rapidly taking up and processing antigens from the environment; they do this by extending processes through intercellular spaces in the epithelium and sampling the airway milieu, a mechanism described as "snorkeling" [28,29]. The increased exposure and activation of DCs could explain the increased prevalence of adaptive T-cell responses such as allergic bronchopulmonary aspergillosis (ABPA) in CF patients [30]. Thus the effect of CFTR and the ASL in regulating antigen uptake in the lung is an area of lung immunology which needs to be explored (Fig.…”
Section: Innate Immunity In Cfmentioning
confidence: 99%